Fabrication of crystalline silica nanoparticles-embedded nanocomposites and their enhanced mechanical, thermal and insulating properties. Issue 13 (September 2019) - Han, Changmin; Im, Hyeon-Gyun; Park, Hoy Yul; Yoon, Seog-Young; Kang, Dong Jun
Abstract: Crystalline silica nanoparticles exhibit superior physical properties to amorphous phase when incorporated in nanocomposites. In this paper, we introduce the crystalline silica nanoparticles–embedded nanocomposites (CSN–nanocomposite) as a high-performance insulation material, and discuss their improved macro/microscopic properties according to the CSN contents. Monodisperse CSN particles (50 nm in size) are produced via facile and cost-effective top-down grinding methods, and their surfaces are modified with organic ligands to endure homogeneous dispersion and chemical crosslinking with epoxy matrix. With the aid of optimal hybridization of the CSN and the matrix, the CSN–nanocomposite exhibits high optical transparency, enhanced mechanical strength, increased thermal conductivity, and improved electrical insulating property.